Welfare-based management of nursing homes to improve the quality of life of the elderly in Tanjungpinang City, Indonesia - Solina, Emmy; Wisadirana, Darsono; Maksum, Ali; Chawa, Anif Fatma; Niko, Nikodemus (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the role of welfare-based management approaches in improving the quality of life for the elderly in nursing homes in Tanjungpinang City, Indonesia, by focusing on how institutional care practices are shaped through a combination of policy implementation, administrative strategies, and human resource dynamics within the context of local socio-cultural values. In particular, the research explores how welfare-oriented management prioritizes the development of personalized care plans, fosters social participation, and ensures access to basic health services as part of a holistic approach to elderly well-being. Using a qualitative approach, it investigates how institutional practices, family involvement, and care frameworks intersect to support elderly well-being. Data were collected through in-depth interviews and observations within selected care institutions. The findings highlight that welfare-oriented management emphasizes individualized care plans, regular health monitoring, and social inclusion through community engagement. These elements collectively promote residents’ physical health, emotional stability, and sense of belonging. However, the implementation of such approaches is constrained by limited resources, staffing challenges, and cultural norms that often view institutional care as a last resort. These obstacles affect the consistency and quality of eldercare services. The study concludes that effective eldercare requires a shared responsibility among the government, families, and institutional actors. Strengthening cooperation between these parties is essential to build an inclusive, sustainable model that meets the diverse needs of the aging population. Practically, this research offers insight into how developing countries can adapt welfare-based eldercare strategies to local contexts. It underscores the urgency of policy reforms and increased investment in eldercare infrastructure, while also advocating for greater public awareness and family participation.